Pengaruh Konsentrasi Ekstrak Daun Mahoni Swietenia mahagoni (L.) Jacq. Terhadap Intensitas Serangan Hemilia Vastatrix Berk. et Broome Penyakit Karat Daun Tanaman Kopi Arabika (Coffea Arabica L.) di Kawasan Hutan Lindung Darajat Kabupaten Garut - Susanti, Siti Rohmah; Rosmaladewi, Okke; Daud, Zulmaida (Media Nusantara, 2021)
Leaf rust caused by the fungus Hemileia vastatrix B. et Br. in Arabica coffee plants is a problem for farmers in Indonesia and in several other countries because it can reduce coffee production by 25%. The improper application of technical culture is one of the causes of the high intensity of leaf rust disease. Mahogany plant Swietenia mahogany (L.) Jacq. Is known to contain limonoid secondary metabolites which can control viruses, fungi, and bacteria. This study aims to determine the effect of the most effective concentration of mahogany leaf extract in controlling leaf rust disease in Arabica coffee varieties. The study was conducted in the protected forest area of Darajat, Garut Regency, in August to October 2019. The method of the study used a Randomized Block Design (RBD), consisting of 5 treatments and 5 replications. The treatments included mahogany leaf extract concentration of 50 gr/L water, 100 gr/L water, 150 gr/L water, 200 gr/L water, and control (without application).